Study on lattice structures using additive manufacturing and its application on a new ultra-lightweight vehicle suspension system - Niu, Jie (2017)
With the increasing development of Additive Manufacturing technologies in the past two decades, the area of lattice structures has received considerable attention due to their inherent advantages in providing lightweight, high stiffness, and strong materials. However, this comes with new challenges such as geometry modelling, optimal selection of unit cell for certain loading condition, and mechanical performance for practical applications. This research provides a systematic investigation of lattice structures from design, testing, to numerical investigation and analytical study, as well as a case study for practical engineering application. A new method to create lattice structures using the traditional CAD package was proposed. It can automatically generate parametric models of complex lattice structures. Three lattice structures with triangular unit cells, cubic unit cells and hexagonal unit cells are shaped by side length, L, strut thickness, t, and height, h (or layer number, n, in h direction). The prototypes manufactured from Nylon and AlSi10Mg show good manufacturability. The experimental tensile curves of the lattice structures reveal distinguished results from the traditional solid materials. The triangular lattice structure was found to be the best in terms of greater effective Young’s modulus (E*) and stiffness-to-mass ratio. The theoretical solution of E*for triangular lattice structure (E*EB) was derived based on Euler-Bernoulli beam theory. The numerical results of E*by using a representative volume element were obtained by Finite Element Analysis (FEA). The effects of L, t and h, on values of E* were investigated independently. The results show that t had the most significant effect. Values of E* obtained by the proposed analytical solution have shown the best agreement with the corresponding FEA results when compared with other existing methods. The experimentally determined values of E* are in excellent agreement with both analytical and numerical solutions. A new single part vehicle suspension with lattice structure was created using Creo®. As the lattice structure suspension is made of scale unit cells shaped by several parameters, it is time-consuming to run simulation with this model. Instead, solid suspension with E* of triangular lattice structure determined by the proposed analytical solution was used in FEA. The optimization method by Design of Experiments (DOE) was used to develop the formulae among design variables (L, t, h and T) and maximum von Mises stress, maximum deformation, stiffness-to-mass ratio and total mass. This method has proven to be an effective way to obtain the mechanical response of large scale lattice structures. The optimum parameters [T, t, L, n] are [2.90, 1.90, 7.82, 1] for the objective of maximum stiffness-to-mass ratio, which is found to be a conservative design. For the objective of minimum total mass, the optimized values are [0.55, 0.76, 4.88, 1], where the design can make full use of structure materials. In the future, these two different lightweight methods should be considered along with other requirements, such as vibration performance and failure behaviour.